Projeto colaborativo em ambientes digitais de atividades de aprendizagem e avaliação para aquisição de competências em informação e documentação - Agustín-lacruz, Maria Del Carmen; Gómez-díaz, Raquel; Fujita, Mariângela Spotti Lopes [UNESP] (Pontifícia Universidade Católica de Campinas, 2011)
The search for international impact and the need to create formal or informal networks of academic cooperation are some of the most common features of the current training offered by many universities. Aware of this difficulty and the desirability of creating synergies to enrich teaching and academic collaboration networks between universities, an experience is presented, in the context of the teaching of Information and Documentation, of inter-university collaboration for the joint design of learning activities and skills assessment, developed by teachers in the public universities of Zaragoza and Salamanca (Spain) and the São Paulo Universidade Estadual Paulista Júlio de Mesquita Filho (São Paulo, Brazil). The experience is developed using models that facilitate the structuring of learning activities aimed at the acquisition of common skills. Each activity that is proposed and developed is recorded in a spreadsheet which collects the information arranged in various fields such as: description, skills, objectives, expected learning outcomes, tools, required resources and materials, evaluation criteria, amongst others, so that the student can see what he is asked to do, how to do it and how useful it will be. This way of designing skills-based learning activities is possible, in geographically diverse academic settings through the use of Information Technology and Communication, enabling both remote cooperation between teachers and also materials offered on the platforms of each of the universities.

A busca de projeção internacional e a necessidade de formar redes formais ou informais de cooperação acadêmica são algumas das características mais comuns da formação atual, oferecidas por várias universidades. Cientes dessa dificuldade, assim como da conveniência da criação de sinergias docentes e do enriquecimento das redes de colaboração acadêmica entre as universidades, é apresentada no contexto de ensino de Informação e Documentação, uma experiência de colaboração interuniversitária para o projeto conjunto de atividades de aprendizagem e avaliação por competências, desenvolvido por docentes das Universidades Públicas de Zaragoza e Salamanca (Espanha) e da Universidade Estadual Paulista Júlio de Mesquita Filho (São Paulo, Brasil). A experiência é desenvolvida por meio de modelos de registros que facilitem a estruturação de atividades de aprendizagem que visam à aquisição de competências comuns. Cada atividade proposta e desenvolvida é registrada em uma planilha que reúne a informação, organizada em diversos campos como: descrição, competências, objetivos, resultados de aprendizagem previstos, ferramentas, recursos e materiais necessários, critérios de avaliação, entre outros aspectos, de maneira que o aluno possa ver o que deve fazer, como fazer e qual a utilidade. Essa forma de conceber as atividades de aprendizagem baseadas em competências é possível, em ambientes acadêmicos geograficamente tão distantes, pelo uso das Tecnologias de Informação e Comunicação, que permitem tanto a colaboração à distância entre os professores quanto o acesso aos materiais oferecidos nas plataformas de cada uma das universidades.
Joint project in digital learning environments and an evaluation in obtaining information and documentation skills
Keywords: Aprendizagem baseada em competências; Espaço europeu de educação superior; Projeto de atividades de aprendizagem; Tecnologia de informação e comunicação; Competence based learning; European higher education area; Design of learning activities; Information technology and communication